2013
DOI: 10.1007/s12011-013-9723-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Serum Zinc, Copper, Manganese, Iron, Calcium, and Magnesium Level and Complexity of Interelement Relations in Generalized Anxiety Disorder Patients

Abstract: The purpose of the study was to determine the concentration of serum trace and other essential elements of generalized anxiety disorder patients and to find out the relationship between element levels and nutritional status or socioeconomic factors. The study was conducted among 50 generalized anxiety disorder patients and 51 healthy volunteers. Patients were selected and recruited in the study with the help of a clinical psychologist by random sampling. The concentrations of serum trace elements (Zn, Cu, Mn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 21 publications
0
22
1
1
Order By: Relevance
“…In contrast to our study, it was also shown that serum magnesium level was significantly higher in patients with mental disorders than control group (Imada et al, 2002). In addition, no statistically significant difference was observed in serum magnesium level between control and case groups in the study by Islam et al on 50 patients with general anxiety disorder and 51 healthy individuals (Islam et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, it was also shown that serum magnesium level was significantly higher in patients with mental disorders than control group (Imada et al, 2002). In addition, no statistically significant difference was observed in serum magnesium level between control and case groups in the study by Islam et al on 50 patients with general anxiety disorder and 51 healthy individuals (Islam et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, some studies have suggested that zinc and magnesium serum level in depressive patients, especially those with PPD, is lower than non-depressed individuals (DiGirolamo & Ramirez-Zea, 2009;Stanislawska et al, 2014;Swardfager et al, 2013). However, some other studies have not suggested any statistically significant relationship between the zinc and magnesium serum levels with depression (Crayton & Walsh, 2007;Islam et al, 2013). The anti-depression feature of zinc and magnesium has been seen in animal studies, including on mice (Kroczka et al, 2001;Mlyniec et al, 2013;Samardzic et al, 2013;Poleszak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Islam et al . () demonstrated that generalized anxiety disorder patients display elevated Cu, Mn, and Fe, but decreased Zn, in serum. In contrast, Yanik et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that abnormal levels of several trace metals are associated with psychiatric disorders. For example, Islam et al (2013) demonstrated that generalized anxiety disorder patients display elevated Cu, Mn, and Fe, but decreased Zn, in serum. In contrast, Yanik et al (2004) found higher Cu and lower Fe and Mn in serum from schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 They play a crucial role in immunity system and alteration of normal homeostasis of these elements in our body may adversely affect different biological processes leading to unwanted complications. 21 Since ancient ages, human are using macro-minerals for their therapeutic effects on skin. 13 Zn is a trace element that is considered as a vital mineral for skin health.…”
Section: Resultsmentioning
confidence: 99%